Maillard reaction with milk proteins reduced the prebiotic activity of 2’-fucosyllactose in a neonatal rat model - Simiao Liu; Yujie Pan; Yaqi Tu; Xin Liu; Chunhua Wu; Jia Liu; Meixi Liu; Cuina Wang; Tiehua Zhang; Fazheng Ren; Xuemei Wang; Hao Zhang (Food Chemistry, 2026)

Silica-induced telomere dysfunction promotes pulmonary fibrosis through the activation of the cGAS-STING pathway - Qiuqian Qian; Simiao Pan; Xiaodong Li; Xiaoxue Gong; Zhaoqiang Jiang; Xing Zhang; Jianlin Lou; Lingfang Feng (Toxicology, 2026)

Maillard reaction impairs the prebiotic properties of 2′-fucosyllactose after conjugation with α-lactalbumin - Simiao Liu; Yaqi Tu; Yujie Pan; Meixi Liu; Jia Liu; Chunhua Wu; Xin Liu; Fazheng Ren; Xuemei Wang; Hao Zhang (International Dairy Journal, 2026)

Unraveling the structure-selectivity nexus: electrode materials for selective phosphorus removal and recovery via capacitive deionization: A systematic review - Sheng Wen; Yu Ma; Yang Fan; Jinxing Lin; Jiaqi Chen; Simiao Li; Huakun Pan; Xinxi Teng; Shupeng Zhang (Chemical Engineering Journal, 2026)

Research of the flow boiling heat transfer on surfaces of stainless steel and anodized-chromium in mini-channel - Luteng Zhang; Jiaxuan Tang; Qiang Lian; Wenbin Xu; Qi Lu; Simiao Tang; Longxiang Zhu; Zaiyong Ma; Wan Sun; Liangming Pan; Meiyue Yan (Annals of Nuclear Energy, 2025)

The nucleation characteristics of geyser boiling in sodium heat pipes - Zaiyong Ma; Qi Wu; Yugao Ma; Simiao Tang; Luteng Zhang; Changwen Liu; Liangming Pan (Annals of Nuclear Energy, 2025)

Integrated DNA methylation analysis of peripheral blood from asbestos exposed populations and patients with malignant mesothelioma reveals novel methylation driver genes of diagnostic and prognostic relevance - Lingfang Feng; Tao Li; Biao Xu; Jing Huang; Hailing Xia; Zhaoqiang Jiang; Junfei Chen; Simiao Pan; Xing Zhang; Hua Jiang; Jianlin Lou (Environmental Pollution, 2024)

Incorporating environmental capacity considerations to prioritize control factors for the management of heavy metals in soil - Yujie Pan; Wenjing Han; Huanhuan Shi; Xiaorui Liu; Shasha Xu; Jiarui Li; Hongxia Peng; Xinwen Zhao; Tao Gu; Chansgheng Huang; Ke Peng; Simiao Wang; et al. (Journal of Environmental Management, 2024)

Priority control factors for heavy metal groundwater contamination in peninsula regions based on source-oriented health risk assessment - Yujie Pan; Hongxia Peng; Qingqin Hou; Ke Peng; Huanhuan Shi; Simiao Wang; Wuhuan Zhang; Min Zeng; Changsheng Huang; Letian Xu; Pengcheng Pi (Science of The Total Environment, 2023)

Effects of choline supplementation on growth performance, liver histology, nonspecific immunity and related genes expression of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) fed with high-lipid diets - Tao Li; Xiaobo Yan; Xiaohui Dong; Simiao Pan; Beiping Tan; Shuang Zhang; Xiangxiang Suo; Weibin Huang; Menglong Zhou; Yuanzhi Yang (Fish & Shellfish Immunology, 2023)

Oil source regulates intestinal health of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu): Structure, inflammation and microorganisms homeostasis - Xiaobo Yan; Hao Liu; Simiao Pan; Beiping Tan; Shuang Zhang; Hongyu Liu; Shuyan Chi; Qihui Yang; Yuanzhi Yang; Xiaohui Dong (Aquaculture, 2023)

Effect of dietary oregano oil on growth performance, disease resistance, intestinal morphology, immunity, and microbiota of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Yu Xin; Hao Liu; Xiaobo Yan; Weibin Huang; Simiao Pan; Menglong Zhou; Baiquan Lu; Beiping Tan; Xiaohui Dong; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The study aimed to investigate the effects of oregano oil (OO) supplement in the diet on the growth performance, disease resistance, immunity, and intestinal health of hybrid grouper. Six isonitrogenous and isolipidic diets were fed to the grouper with an initial weight of 19.10 ± 0.12 g for 8 weeks, of which the dietary OO levels were 0 (Control), 0.1 (OO-0.1), 0.3 (OO-0.3), 0.6 (OO-0.6), 0.9 (OO-0.9), or 1.2 (OO-1.2) g kg -1 . The results showed that there were no significant differences in growth performance among the six groups, while the OO supplement could improve the disease resistance ability of grouper. Our findings have demonstrated that the OO supplement, especially 0.3 g kg -1 , could improve the intestinal morphology via increasing the villus number and muscle thickness and elevate digestive enzyme activities such as those of amylase (AMS) and lipase. The 0.3-g kg -1 OO supplement also can activate the antioxidant defense system, reduce nuclear factor erythroid 2-related factor 2-like 2 (Nrf2)/Kelch-like-ECH-associated protein 1 (Keap1) expression, and then enhance the immune ability via acid phosphatase (ACP), lysozyme (LYS), complement C3 (C3), and tight junction-associated signaling pathways in hybrid grouper. Meanwhile, the relative abundance of Firmicutes and Bacteroidetes in the OO-0.3 group was significantly higher than that of Control group ( P < 0.05), while the relative abundance of Proteobacteria showed a basically opposite trend ( P < 0.05). These findings suggested that dietary OO supplementation could significantly improve intestinal health and induce the antioxidant defense system and immunity, which means that OO could be used as a functional feed additive to protect the intestine, and the appropriate addition level of OO should be 0.3 g kg -1 .

Low Concordance Between Blood Pressures Measured in Periodic Health Examinations and in a Workplace-Based Hypertension Management Program - Jun-Xiang Chen; Yan-Feng Zhou; Tingting Geng; Simiao Chen; Shuohua Chen; Guodong Wang; Yan-Bo Zhang; Yi Wang; Zhou-Zheng Tu; Gang Liu; Shouling Wu; An Pan (Phenomics, 2022)

Lipid metabolism disorders of hybrid grouper (♀Epinephelus fuscointestinestatus × ♂E. lanceolatu) induced by high-lipid diet - Xiangxiang Suo; Xiaobo Yan; Beiping Tan; Simiao Pan; Tao Li; Hao Liu; Weibin Huang; Shuang Zhang; Yuanzhi Yang; Xiaohui Dong (Frontiers in Marine Science, 2022)
This study investigated the effect of lipid levels on growth, body composition, lipid metabolism enzymes activity and related genes expression in hybrid grouper (♀ Epinephelus fuscointestinestatus × ♂ E. lanceolatu ). Three diets with different lipid levels of 6% (low-lipid feed, LF), 11% (medium-lipid feed, MF) and 16% (high-lipid feed, HF) were designed and each diet was fed to triplicate groups of 30 fish each (6.73 ± 0.00g) for eight weeks. The results revealed the following. 1) The maximum weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER) and the lowest feed conversion ratio (FCR) values were found in the HF group. There was no significant difference in the survival rate (SR) among the groups ( P > 0.05). 2) Condition factor (CF), hepatosomatic index (HSI) and visceralsomatic index (VSI) increased with increasing dietary lipid. 3) Crude lipid content in the whole-body and muscle increased significantly as the dietary lipid level increased ( P < 0.05). 4) Principal component analysis of fatty acids showed that sum n-3 polyunsaturated fatty acids (∑n-3PUFA)/sum n-6 polyunsaturated fatty acids (∑n-6PUFA) was significantly higher in the HF group than in the other two groups ( P < 0.05). 5) Biochemical serum indexes showed higher triglycerides (TG), total cholesterol (TC), alkaline phosphatase (AKP) and low-density lipoprotein-cholesterol (LDL-C) levels but lower high-density lipoprotein-cholesterol (HDL-C) level in the HF group. 6) Liver lipid metabolism enzymes activity and biochemical indicators showed that fish fed the MF diet had higher lipoprotein lipase (LPL), hepatic lipase (HL) and triglyceride lipase (ATGL) activity but lower fatty acid synthase (FAS) activity and very-low density lipoprotein-cholesterol (VLDL-C) level. 7) The relative expression levels of lipoprotein lipase ( lpl ), adipocyte-type fatty acid-binding protein ( a-fabp ), liver-type fatty acid-binding protein ( l-fabp ), heart-type fatty acid-binding protein ( h-fabp ) and hormone-sensitive lipase ( hsl ) genes in the fish liver were higher in the MF group with increasing dietary lipid ( P < 0.05), while the fatty acid synthase ( fas ) gene was expressed at lower relative level ( P < 0.05). 8) Histological oil-red sections of the liver showed that fish in the HF group had larger and more hepatic lipid droplets than those fed the other diets. It was concluded that fish fed the HF diet had better growth performance but this diet was not conducive to the progress of lipid metabolism, resulting in lipid accumulation and affecting the quality of the fish. This study provides useful information for the formulation of environmentally friendly and cost-effective diets for hybrid grouper.

Effects of vitamin E supplementation of a high-lipid diet on the growth and biochemical parameters of hybrid groupers (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatus) - Weibin Huang; Xiaobo Yan; Hao Liu; Beiping Tan; Xiangxiang Suo; Simiao Pan; Tao Li; Yuanzhi Yang; Xiaohui Dong (Frontiers in Marine Science, 2022)
There is a trend towards using high-lipid diets in aquaculture, which can be optimized by using certain additives. This study investigated the effect of vitamin E (VE) supplementation of a high-lipid diet on the growth, serum and liver biochemical indexes, hepatic histology, and lipid metabolism of hybrid groupers (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ). Six groups of iso-protein (50.23%) and iso-lipidic high-lipid (15.36%) experimental diets were prepared by adding VE at concentrations of 49.6 (basic diet, controls), 100, 110, 163, 206, and 245 mg/kg. Each treatment consisted of three replicates and 30 fish (10.20 ± 0.02 g) in an 8-week feeding experiment. The results show that 1) compared with controls, growth performance was not affected by VE addition. However, the weight gain rate (WGR) and specific growth rate (SGR) were significantly lower in the high-VE group (245 mg/kg) than in the 163 and 206 mg/kg groups. 2) Compared with controls, VE significantly increased the contents of alpha-tocopherol in the liver and muscle. 3) Adding VE can reduce the fatty livers caused by high-lipid diets and significantly reduce total serum cholesterol, reduce the activity of lipid synthesis enzymes, and significantly increase the activity of lipolytic enzymes in the liver. 4) Compared with controls, appropriate amounts of VE significantly increased the expressions of the liver lipid-metabolism-related genes PPAR-α , PPAR-β , PPAR-γ , H-FABP , A-FABP , and L-FABP . Based on observations of lipid metabolism enzyme activity, histological sections, and lipid-metabolism-related gene expression, we conclude that the addition of 163–206 mg/kg VE to a high-lipid diet can promote lipid metabolism in groupers.

Amelioration of Flesh Quality in Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu) Fed With Oxidized Fish Oil Diet by Supplying Lactobacillus pentosus - Xiaobo Yan; Simiao Pan; Zhihao Li; Xiaohui Dong; Beiping Tan; Shuisheng Long; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2022)
The objective was to investigate the improvement of the flesh quality and nutritional value of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ E. lanceolatu ) by Lactobacillus pentosus (BL-15). The two diets were prepared with 9% oxidized fish oil (OFO negative control group) or 9% fresh fish oil (FFO positive control group) as the major lipid source, and the OFO diet were sprayed with L. pentosus at 1.0×10 7 , 1.0×10 8 , 1.0×10 9 CFU/g, respectively. Five kinds of diets were fed to hybrid grouper with initial weight of 21.36 ± 0.03 g for 60 days. The results showed that (1) consumption of OFO diet significantly increased muscle crude lipid, total cholesterol, and total monounsaturated fatty acids contents and significantly decreased muscle C20:5n3, C22:6n3, ∑PUFA levels of grouper ( p < 0.05), whereas the addition of L. pentosus to OFO diet significantly reduced muscle crude lipid, malondialdehyde, reactive oxygen radicals, total cholesterol concentration, increased C20:5n3, C22:6n3, ∑PUFA levels, increased muscle crude protein content, and enhanced muscle hardness, gumminess, and chewiness compared with FFO or OFO group ( p < 0.05). (2) In addition, ingestion of OFO diet significantly increased muscle phenylalanine content and significantly decreased aspartic acid content ( p < 0.05), while the addition of L. pentosus restored aspartic acid to the level not significantly different from that of FFO group ( p > 0.05). The addition of L. pentosus also increased tyrosine, lysine, leucine, phenylalanine, arginine, and alanine content compared to FFO group at the same time ( p < 0.05). (3) Furthermore, the intake of OFO diet would lead to deterioration in muscle flavor quality and increase in noxious odors in grouper, and the addition of L. pentosus can mitigate or rectify these detrimental consequences. In further analysis, consumption of OFO group significantly downregulated the mRNA expression of muscle growth factors and caused serious damage to the muscle antioxidant system ( p < 0.05), which was protected against by the potent antioxidant properties of L. pentosus . We recommend the supplementation level of L. pentosus to be 1.0×10 9 CFU/g under the highly oxidized conditions of the present trial fish oil.

The Effect of Oxidized Fish Oil on the Spleen Index, Antioxidant Activity, Histology and Transcriptome in Juvenile Hybrid Grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus) - Shuisheng Long; Zhihao Li; Xiaohui Dong; Xiaobo Yan; Hao Liu; Beiping Tan; Shuang Zhang; Simiao Pan; Tao Li; Xiangxiang Suo; Yuanzhi Yang (Frontiers in Marine Science, 2021)
The spleen is an important organ in the immune function of fish, and it is also important for hematogenesis and antibody and granulocyte production. However, the effect of oxidized fish oil on the spleen of hybrid grouper (♀ Epinephelus fuscoguttatus × ♂ Epinephelus lanceolatus ) is unknown. In this study, hybrid groupers were fed with oxidized fish oil and the spleen index, antioxidant ability, histology and transcriptome were investigated. Oxidized fish oil did not affect the spleen index. Levels of superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px) and malondialdehyde (MDA) in the spleen were significantly increased as the amount of oxidized fish oil in the diet increased, but the vitamin E concentration was significantly decreased. The morphological organization of the spleen was damaged with increased oxidative stress. And the spleen reacted to oxidative stress by platelet activation, FOXO and notch signaling pathways, which involved amyloid beta precursor protein binding family B member 1 interacting protein (APBB1IP) gene, glucose-6-phosphatase (G6PC) gene, histone acetyltransferase p300 (EP300) gene, insulin gene and notch 2 gene. In conclusion, the oxidized fish oil caused oxidative stress and damaged its structure. Additionally, oxidized fish oil changed the transcription profile of the spleen.